Problem Childfree Ditinjau Dari Worldview Islam - Hidayat, Ahmad Agus; Nurhayati, Nurhayati; Al Farabi, Fahmi Akhyar; Nugroho, Allam Setiawan (CENDEKIA: Jurnal Studi Keislaman, 2023)
Childfree, as a phenomenon, emerged from Western issues concerning women, such as the rise of feminism, social equality, political campaigns about body autonomy, and so on. The term "childfree" began to evolve in the late 20th century, giving rise to the stigma that couples have the right to decide not to have children to address population excess. The childfree phenomenon has become controversial in society, making it interesting to explore further through an Islamic worldview. The method used in this research is qualitative descriptive with a literature review approach from various reliable sources, including books, journal articles, and more. The study's results indicate that women hold an esteemed position in Islam as mothers and contributors to civilization. In the Islamic worldview, a child is considered a trust and a gift from Allah SWT, highlighting the crucial responsibility of parents in their upbringing. Thus, family and offspring form a foundation that needs strengthening in society to continue human life. The presence of childfree choices has negative social impacts, affecting declining birth rates, mental health, and overall quality of life. Therefore, there is a need to reconstruct the childfree phenomenon in line with the Islamic worldview to restore balance in life.